Energy Demand and Available Technologies Analysis for District Heating Cooling Applications in a Science and Technology Park (PTA) in a Mediterranean country - Zubizarreta, Rogelio; Jiménez-Navarro, Juan-Pablo (My University, 2011)
The purpose of this paper is to present the results of the feasibility study for a district heating-cooling network to cover the energy demand in a Science and Technology Park under Mediterranean climate conditions. To evaluate the energy demand a bottom-up strategy has been followed: a building inventory has been carried out to define several building types according to use; envelope and glazing. Energy + has been used to obtain heating and cooling demand profiles for each building type and orientation. According to municipal development plans for PTA and forecast in business growth; the energy demand evaluation in a 10-years timeframe has been carried out. Most appropriate technologies has been analyzed and evaluated: Cogeneration (gas turbine and alternative internal combustion engines); biomass boiler and conventional technologies have been evaluated with TRNSYS to obtain consumption profiles; consumption rates; efficiency indicators and energy losses. Finally an economic analysis has been done to technologies in a 20 years period to evaluate technology that better economic results address. The main objective of this work is the promotion of the efficient and effective energy supply in areas with high energy consumption. DCH technology is widely used in the North of Europe and this paper try to demonstrate that this technology could be apply in Mediterranean areas successfully.
Keywords: Recursos energéticos; Energía - Conservación; District heating cooling:; DHC; Building energy analysis; Energy demand; Technical and feasibility study; District energy; Thermal energy generation.